2005
DOI: 10.1111/j.1365-2419.2005.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Corals of the Aleutian Islands

Abstract: A unique feature of the benthic habitat in the Aleutian Islands is the presence of a highly diverse and abundant coral and sponge community. These communities likely provide important habitat for a variety of fish and invertebrate species. Summaries of historical data and recent direct observations with a submersible indicate that the Aleutian Islands may harbour the highest diversity and abundance of coldwater corals in the world. There are 69 documented taxa (species and subspecies) of coral in the Aleutians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 15 publications
1
59
0
4
Order By: Relevance
“…Examination of specimens collected during that study, from fi shery surveys, and from fi shery bycatch revealed that the Aleutian Islands harbored a diversity of coldwater corals that was extraordinary for a high-latitude ecosystem and that at least 51 species or subspecies of hydrocorals and gorgonians were endemic to the region (Stone and Shotwell, 2007). Corals are widespread on the continental shelf and slope throughout Alaska, but strong evidence indicates that a major shift in coral abundance and species diversity occurs west of the Alaska Peninsula (Heifetz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of specimens collected during that study, from fi shery surveys, and from fi shery bycatch revealed that the Aleutian Islands harbored a diversity of coldwater corals that was extraordinary for a high-latitude ecosystem and that at least 51 species or subspecies of hydrocorals and gorgonians were endemic to the region (Stone and Shotwell, 2007). Corals are widespread on the continental shelf and slope throughout Alaska, but strong evidence indicates that a major shift in coral abundance and species diversity occurs west of the Alaska Peninsula (Heifetz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ocean, and many other areas have shown that some species of cold-water corals build complex structures and produce unique demersal communities in the same way as do shallow-water coral reefs (Heifetz 2002;Heifetz et al 2005;Lundsten et al 2009;McClain et al 2010;Mol et al 2002;Morris et al 2013;Reed et al 2006;Roberts et al 2006;Stone et al 2015). Such frameworks of coldwater corals provide habitats or spawning and nursery grounds for fish and many other animals and thereby support diverse ecosystems (Baillon et al 2012;Roberts et al 2006).…”
Section: Megafaunal Composition Of Cold-water Corals and Other Deep-smentioning
confidence: 99%
“…Recent developments in deep-sea surveys that use acoustic and submersible devices have revealed the widespread distribution of cold-water corals on the deepsea floor throughout the world ocean (Heifetz et al 2005;Lundsten et al 2009;McClain et al 2010;Mol et al 2002;Reed et al 2006;Roberts et al 2006). Reports from…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this contention is another group of benthic marine invertebrates that tends to occur in deeper water (most abundant from 100-200 m depth) (Stone, 2006) and that shows relatively high diversity analogous to that of Monoporella in the Aleutians. The species diversity of a diverse assemblage of skeleton-forming benthic cnidarians (the so-called "coldwater corals," including stylasterines, gorgonaceans, stoloniferans, pennatulaceans, alcyonaceans, and scleractinians) increases sharply west of Samalga pass (~169°W) (Heifetz et al, 2005). Several of these taxa have apparently undergone high levels of speciation in the Aleutians, resulting in a high number of endemics (Heifetz et al, 2005).…”
Section: Local-radiation Hypothesismentioning
confidence: 99%
“…The species diversity of a diverse assemblage of skeleton-forming benthic cnidarians (the so-called "coldwater corals," including stylasterines, gorgonaceans, stoloniferans, pennatulaceans, alcyonaceans, and scleractinians) increases sharply west of Samalga pass (~169°W) (Heifetz et al, 2005). Several of these taxa have apparently undergone high levels of speciation in the Aleutians, resulting in a high number of endemics (Heifetz et al, 2005).…”
Section: Local-radiation Hypothesismentioning
confidence: 99%